Critical in vivo roles of histamine and histamine receptor signaling in animal models of metabolic syndrome. Issue 12 (11th November 2016) - Yamada, Sohsuke; Tanimoto, Akihide; Sasaguri, Yasuyuki
Abstract: Histamine, a classic low‐molecular‐weight amine, is synthesized from L‐histidine by histidine decarboxylase (HDC), and histamine‐specific receptors (HRs) are essential for its actions. Our serial in vivo studies have uniquely reported that expression of histamine/HRs is variably identified in atherosclerotic lesions, and that HDC ‐gene knockout mice without histamine/HRs signaling show a marked reduction of atherosclerotic progression. These data have convinced us that histamine plays a pivotal role in the pathogenesis of atherosclerosis. Among four subclasses of HRs, the expression profile of the main receptors (H1/2R) has been shown to be switched from H2R to H1R during monocyte to macrophage differentiation, and H1R is also predominant in smooth muscle and endothelial cells of atheromatous plaque. Using various animal models of H1/2R –gene knockout mice, H1R and H2R were found to reciprocally but critically regulate not only hypercholesterolemia‐induced atherosclerosis and injury‐induced arteriosclerosis, but also hyperlipidemia‐induced nonalcoholic fatty liver disease (NAFLD). Metabolic syndrome manifests obesity, dyslipidemia, insulin resistance, atherosclerosis, and/or NAFLD, i.e. the dysregulation of lipid/bile acid/glucose metabolism. Therefore, although its etiology is complicated and multifactorial, histamine/HRs signaling has a close relationship with the development of metabolic syndrome. We herein review diverse, key in vivo roles of histamine/HR signaling in the pathogenesis of metabolic syndrome.